Gaspar van Weerbeke: Perspektives on his Life and Music (2019)
This book is the first collection of research articles dedicated exclusively to the life and works of the Renaissance composer Gaspar van Weerbeke. While the basic facts of Gaspar's life have long been known, the book fleshes out the details, presenting a more differentiated and complex picture of his biography. Analysis of a wider range of Gaspar's compositional output leads to new interpretations of his approach to different genres: masses, motets, and motet cycles.